2003
DOI: 10.5713/ajas.2003.227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Chromium Picolinate Supplementation on Growth Performance and Immune Responses of Broilers

Abstract: Two experiments were conducted to evaluate the effects of chromium (Cr) on the growth performance, bone trait, serum traits, and immune responses in broilers. The broilers were fed corn-soybean meal basal diet supplemented with Cr at level of 0 (control), 200, 400, or 800 ppb in the form of chromium picolinate (CrPic). The broilers were fed treated diets for 6 weeks in Exp. 1, but the Cr supplement was removed for the last 3 weeks in Exp. 2. Exp. 1 showed that dietary supplement of Cr did not affect growth per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 23 publications
4
14
1
1
Order By: Relevance
“…Several researchers observed significant improvement in feed conversion ratio of broiler chickens by the addition of Cr supplement (Hossain et al, 1998;Lee et al, 2003). The results of current study indicate that chromium polynicotinate supplementation did not affect the feed conversion ratio of broilers from 10 to 28 days of age.…”
Section: Resultscontrasting
confidence: 59%
“…Several researchers observed significant improvement in feed conversion ratio of broiler chickens by the addition of Cr supplement (Hossain et al, 1998;Lee et al, 2003). The results of current study indicate that chromium polynicotinate supplementation did not affect the feed conversion ratio of broilers from 10 to 28 days of age.…”
Section: Resultscontrasting
confidence: 59%
“…Resultados semelhantes foram verificados por Oba et al (2007), em frangos de corte alimentados com 0, 400, 800 e 1.200 μg Cr/kg na forma de cromo complexado à levedura, e Chen et al (2001), que suplementaram dietas para perus com cromo nicotinato nos níveis de 0, 1 e 3 mg /kg, e não verificaram efeitos do cromo sobre o peso das aves, o consumo de ração e a conversão alimentar. Lee et al (2003) Depois de 24 horas post mortem, as amostras dos peitos das aves foram avaliadas para determinação do pH, o qual não sofreu qualquer alteração atribuível ao nível de cromo da dieta. Os valores de pH estão dentro da faixa considerada normal, ou seja, superior a 5,7 e inferior a 6,2.…”
Section: Resultsunclassified
“…The role of chromium in the immune responses of mammals and chicken is well established (Burton et al, 1993;Lee et al, 2003). It has also been reported that chromium modulates the immune response through its effect on cytokine release (Wang et al, 1996).…”
Section: The Effects Of Different Levels Of Nanocrpic On Immune Respomentioning
confidence: 99%